Implementasi Program Pelatihan Kerja Pemerintah dalam Penyiapan Tenaga Kerja (Studi Kasus pada Balai Latihan Kerja (BLK) Dinas Tenaga Kerja & Transmigrasi Kab. Pohuwato) - Hasman Umuri; Edy Sijaya (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This study aims to determine the implementation of the Government Job Training Institution Program in preparing the workforce, with a case study at the Job Training Center (BLK) of the Manpower & Transmigration Office of Pohuwato Regency. The research method used is qualitative descriptive. The informants in this study include the Head of Service, Secretary of Service, Head of Section, Instructor, and Training Participants. The sampling technique used was purposive sampling, which is a sample determination technique based on research considerations related to the object under study. Data were collected through direct interviews and observation, then analyzed using qualitative descriptive analysis. The results of the study indicate that the implementation of the Government Job Training Institution Program in preparing the workforce in Pohuwato Regency is a very important activity to improve the knowledge of job seekers and those who are already working. The success of this program is highly determined by several indicators such as Training Objectives, Materials, Methods Used, Training Participants, and Trainer (Instructor) Qualifications. Based on findings in the field, the qualifications of trainers (instructors) need to be improved, and it is even recommended to bring in trainers from outside the region to increase and expand participants' insights and apply updated materials.